High Rates of Occult Fallopian Tube Cancer Diagnosed at Prophylactic Bilateral Salpingo-Oophorectomy. Issue 5 (1st July 2009) - Hirst, Jane E.; Gard, Gregory B.; Mcillroy, Kirsty; Nevell, David; Field, Michael
Abstract : Objective: To determine the rate of occult malignancy in patients undergoing prophylactic bilateral salpingo-oophorectomy in Northern Sydney. Methods: A retrospective case series of 45 consecutive patients who underwent prophylactic bilateral salpingo-oophorectomy between 2004 and March 2008. Results: Five (11%) cases of occult neoplasia were found in 45 patients. This included 3 cases of micro-invasive serous carcinoma of the fallopian tube, 1 case of in situ carcinoma in the fallopian tube and 1 case of metastatic breast cancer in the ovary. All cases of primary neoplasia were in the fimbrial end of the fallopian tube. Conclusions: The importance of complete removal of the fallopian tubes and ovaries and the rigorous systematic pathological examination of these specimens are demonstrated in this case series. It supports emerging evidence that the fimbrial end of the fallopian tube is an important site of genesis of cancer in BRCA1/2 mutation carriers